Characteristics of Maxillofacial Fractures Resulting from Road Traffic Accidents at Dr. Hasan Sadikin General Hospital - Caesario, Oldi; Boesoirie, Shinta Fitri; Tahid, Alwin (Althea Medical Journal, 2017)
Background: Maxillofacial fracture is a serious injury in the head region which is frequently found in the emergency room. In Indonesia, the road traffic accident is the main etiology. Epidemiological assessments are important to assess trends and set the priorities for treatment and prevention of the injury. This study was conducted to identify the characteristics of maxillofacial fracture resulting from road traffic accidents. Methods: This descriptive retrospective study involved hospitalized patients with maxillofacial fracture resulting from road traffic accidents at Dr. Hasan Sadikin General Hospital in 2011â2013 using the total sampling technique. Data were collected in the period AugustâOctober 2014 which included patient demographics, detailed description of the accident and the fracture.Results: A total of 187 patients with male/female ratio of 5:1 and a mean age of 26.78 year. The majority of patients were motorcyclists (92%) with most of them were not wearing safety equipment. Most of the accidents took place in 2011 in Bandung. Mandible was the most common site of injury followed by the maxilla and nasal bone. Open reduction was performed in 69.52% patients).Conclusions: Maxillofacial fracture is more common in men with the mean age of 26.78 years. The majority of patients are motorcyclists. Most of them are not using safety equipment. Most of the accidents occurred in Bandung in 2011. Mandible is the most common site of fracture. Open reduction is the most commonly performed treatment